Replication DHS 2005 climate dataset - Greßer, Christina; Meierrieks, Daniel; Stadelmann, David (Multiplicity in Decision-Making of Africa's Interacting Markets: The Functioning of Community Law, the Role of Market Participants and the Power of Regional Judges (MuDAIMa), 2021)
Associated main article: 20210211_TempEconDevelopment_article.pdf
Keywords: Natural disasters; Global warming; Sustainability; Disaster Management; Environmental Accounts; Environmental Accounting; Environmental Equity; Population Growth; Regional Economic Development; Regional Economic Change; Economic-Environmental Interactions; Trade; Environment; Climate Change; Econometric Evidence